Religious-Based Higher Education Institution and Human Resource Development: A Case Study of Universitas Pesantren Tinggi Darul Ulum Jombang (UNIBDU) - maarif, samsul (Pascasarjana IAIN Pontianak, 2018)
The role of higher education is very crucial in developing human resource because it is a future investment which has great effect on the improvement of real sector. Higher education is proven to be an effective agent of social change. In human resource management, the role of higher education is embodied in community service program which is more known as “Tri Dharma Perguruan Tinggi” including acquisition, transmission and application. Human Resource management is basic administrative description or educational management based on a series of interrelated processes in guiding the behavior of individuals as the member of an organization in order to achieve its goals. The process can be identified as follows: planning, compensation, recruitment, selection, induction, appraisal, development, maintenance, performance, security, integration, and information.